Między tradycją a nowoczesnością: Jubileusz 60-lecia Stowarzyszenia Absolwentów Uniwersytetu Jagiellońskiego (1964–2024) - Stinia, Maria (2024)
BETWEEN TRADITION AND MODERNITY: 60 YEARS OF THE JAGIELLONIAN UNIVERSITY ALUMNI ASSOCIATION (1964–2024)The Jagiellonian University Alumni Association, established in 1964, was founded and developed thanks to graduates who had the vision to maintain ties with their Alma Mater and continually contribute to it. Among the founders were representatives of all fields of study. The Association was also open to graduates of the departments that were abolished or separated from the University by the communist authorities in the 1950s, and thanks to them, the idea of the pre-war Jagiellonian University was preserved. The main statutory tasks of maintaining ties with the University, undertaking various forms of social activities for its benefit, popularizing its traditions and achievements as well as helping to organize scientific and self-education efforts of its members have been consistently carried out to this day. In the first period after the establishing, the organization focused on creating structures (including a dozen regional branches) and setting the tone of its activity. The initiatives taken were of a popular-scientific, cultural, educational, tourist, and sightseeing nature. The modes of activity followed good intelligentsia models of regular contact with theater, poetry, prose, and music. The imposition of martial law in 1981 halted the work of the Association, severed contacts and limited its functioning, which resulted in a significant decline in the number of members. As soon as it became possible, efforts were made to restore normal operations. At present, the Association’s activity is based on extensive self-education of its members, active participation in the life of the University and undertaking urban space actions.
Keywords: Jagiellonian University; Jagiellonian University Alumni Association; alumni; anniversary